2014
DOI: 10.1097/qad.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

HIV Tat acts on endogenous retroviruses of the W family and this occurs via Toll-like receptor 4

Abstract: In-vivo consequence of the study could be that, through increase of CD16 and CCR2, Tat promotes neuroinvasion not only by HIV-infected monocytes/macrophages but also by the HERV-Ws, with their neuropathogenic potential. Also, the novel finding of TLR4 stimulation by Tat may be of relevance, as TLR4 is critical in neuroinflammation. Within central nervous system (CNS), Tat-induced TNFα could induce high levels of the HERV-Ws, in both macrophages and astrocytes, also without HIV replication. The indirect mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 62 publications
1
47
0
2
Order By: Relevance
“…A major difference is that only MSRV is found as complete extracellular virus, while syncytin-1 is found only intracellularly or on the plasma membrane [16]. At the protein level, no antibodies discriminating MSRVenv and syncytin-1 are yet available [28]. At the RNA level, MSRVenv and syncytin-1 have 94% similarity; we observed that MSRVenv sequences have a 12-nucleotide insertion in the trans-membrane moiety [29].…”
Section: The Herv-w Family: Msrv and Syncytin-1mentioning
confidence: 71%
See 4 more Smart Citations
“…A major difference is that only MSRV is found as complete extracellular virus, while syncytin-1 is found only intracellularly or on the plasma membrane [16]. At the protein level, no antibodies discriminating MSRVenv and syncytin-1 are yet available [28]. At the RNA level, MSRVenv and syncytin-1 have 94% similarity; we observed that MSRVenv sequences have a 12-nucleotide insertion in the trans-membrane moiety [29].…”
Section: The Herv-w Family: Msrv and Syncytin-1mentioning
confidence: 71%
“…Since 10% of healthy Caucasian release MSRV in the blood [16], we wondered whether MSRV and syncytin-1 are activated by HIV and thus whether their neuropathogenic and immunopathogenic properties could contribute to HIV-related neurodegeneration [28]. In fact, rather than HIV itself, as the virus production is too low to explain the extensive CNS disease often observed, mechanisms of amplification of toxicity and inflammation in response to HIV infection were suggested as a major cause of neurological disease [64].…”
Section: Msrv/herv-w/syncytin-1 Endogenous Retroviruses and Hiv-relatmentioning
confidence: 99%
See 3 more Smart Citations